2006
DOI: 10.1089/ars.2006.8.1865
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Oxidative Stress

Abstract: Oxidative stress is often defined as an imbalance of pro-oxidants and antioxidants, which can be quantified in humans as the redox state of plasma GSH/GSSG. Plasma GSH redox in humans becomes oxidized with age, in response to oxidative stress (chemotherapy, smoking), and in common diseases (type 2 diabetes, cardiovascular disease). However, data also show that redox of plasma GSH/GSSG is not equilibrated with the larger plasma cysteine/cystine (Cys/CySS) pool, indicating that the "balance" of pro-oxidants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
1,061
4
45

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,462 publications
(1,134 citation statements)
references
References 61 publications
24
1,061
4
45
Order By: Relevance
“…Taken together, our results showed that both Med and CHO-PUFA diets increase the postprandial gene expression profile of the antioxidant defense system, and therefore the ROS detoxification rate in the adipose tissue, as compared to an SFA-rich diet. In line with the adipose tissue gene expression results, our study showed that the consumption of Med and CHO-PUFA diets reduces postprandial oxidative stress in elderly people, on the basis of the higher values found after the consumption of Med and CHO-PUFA diets as compared to an SFA-rich diet in postprandial plasma GSH levels and the GSH/GSSG ratio, a parameter that correlates with biological redox status (Jones 2006) and decreases as a consequence of glutathione oxidation (Jones 2002). Additionally, the measurement of two other oxidative stress biomarkers, isoprostanes and lipoperoxides, both of which oxidative stress-derived molecules, supports this idea.…”
Section: Discussionsupporting
confidence: 81%
“…Taken together, our results showed that both Med and CHO-PUFA diets increase the postprandial gene expression profile of the antioxidant defense system, and therefore the ROS detoxification rate in the adipose tissue, as compared to an SFA-rich diet. In line with the adipose tissue gene expression results, our study showed that the consumption of Med and CHO-PUFA diets reduces postprandial oxidative stress in elderly people, on the basis of the higher values found after the consumption of Med and CHO-PUFA diets as compared to an SFA-rich diet in postprandial plasma GSH levels and the GSH/GSSG ratio, a parameter that correlates with biological redox status (Jones 2006) and decreases as a consequence of glutathione oxidation (Jones 2002). Additionally, the measurement of two other oxidative stress biomarkers, isoprostanes and lipoperoxides, both of which oxidative stress-derived molecules, supports this idea.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding PPNs-SO 3 H adducts, which were reported here for the first time, we found no straightforward explanation to interpret the interplay between nitrone structure and (a H , a P ) variations. Again, strong STW differences were found among these spin adducts, e.g., it was of 6.85 mT for 2-CF 3 -PPN-SO 3 H and 7.33 mT for 4-OH-3,5-OMe-PPN-SO 3 H with a P values as different as 3.990 and 4.479 mT, respectively ( Figure 3A,B).…”
Section: Introductionmentioning
confidence: 95%
“…Many triggers of ROS formation have been identified, such as activation of endogenous enzymes (e.g., xanthine or NADPH oxidases) or exposure to UV light, ionizing radiations, toxins, cigarette smoke or environmental pollutants [1]. The concept of oxidative stress was recently re-defined as a disruption of redox signaling and control, a new perception that stimulated many investigations toward the role of cellular nucleophiles such as glutathione, or the identification of key enzymes perturbations [2][3][4]. Although it was now established that low levels of certain ROS can enhance cell defense capacity [2,5], there is a tremendous body of evidence from animal studies and clinical trials that a massive release of ROS contribute to the initiation and progression of a variety of chronic diseases such as inflammation, cancer, cardiovascular and neurodegenerative disorders, or acute iron overload-induced poisoning [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent evidence indicates that the disruption of redox signaling is an important aspect of oxidative stress, sometimes more important than the pro-oxidant-antioxidant imbalance or the tissue damage induced by such imbalance. 68 Therefore, a new definition of oxidative stress has been proposed as 'an imbalance between oxidants and antioxidants in favor of the oxidants, leading to a disruption of redox signaling and control and/or molecular damage' . 68 Consequences of oxidative stress can be very subtle to very serious (including oxidative damage to biomolecules, disruption of signal transduction, mutation and cell death), depending on the balance between reactive species generation and antioxidant defense.…”
Section: Contribution Of Inflammation and Oxidative Stress To Dr And mentioning
confidence: 99%
“…68 Therefore, a new definition of oxidative stress has been proposed as 'an imbalance between oxidants and antioxidants in favor of the oxidants, leading to a disruption of redox signaling and control and/or molecular damage' . 68 Consequences of oxidative stress can be very subtle to very serious (including oxidative damage to biomolecules, disruption of signal transduction, mutation and cell death), depending on the balance between reactive species generation and antioxidant defense. 69 Oxidative stress can be estimated by production of a pro-oxidant, such as superoxide; expression or activity of an antioxidant, like superoxide dismutase or damage induced by oxidative stress to biomolecules, such as protein (nitration of tyrosine residues-nitrotyrosine), lipids (aldehydes from lipid peroxidation) and DNA (8-hydroxy-2¢-deoxyguanosine, 8-OHdG).…”
Section: Contribution Of Inflammation and Oxidative Stress To Dr And mentioning
confidence: 99%